MEDIA SOFTWARE MUSIK STUDIO ONE SEBAGAI ALTERNATIF PEMBELAJARAN SENI MUSIK TRADISIONAL PADA MAHASISWA SENDRATARIK PGRI PALEMBANG - Putra, Rio Eka (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Creating a musical work can not only be done in groups but can be done individually, like the example of using music software that is developing now. A composer / creator can produce a piece of music with the form of an mp3 media player. The music software is equipped with various sounds such as the sound of violins, guitars, drums etc. In the Software it also has sounds from traditional traditions of musical instruments in Indonesia and the world. Regional music or traditional music is music that was born and developed in areas throughout Indonesia. The distinctive feature of this type of music is the song content and the instrument (the instrument). Traditional music has distinctive characteristics, namely poetry and melodies using local language and style. Traditional art which is identity, identity, media expression of the community. Learning by means of new innovations based on the construktivistic paradigm, help student to get a new understanding and can develop ideas widely and suport student independence in explisit discusion.